If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 23 + -5 + -5 = 0 Combine like terms: 23 + -5 = 18 18 + -5 = 0 Combine like terms: 18 + -5 = 13 13 = 0 Solving 13 = 0 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| (3x-5)(x+3)=(3x-5)(-3x-1) | | -9x-45=171 | | 0.4x-4=0.05x+3 | | -47-5x=-137 | | 1=5n-3-1 | | 0.3x-1=0.5x+4 | | 2y-5n= | | 24+8x=-96 | | -4K+3=-13 | | 10x+61=-59 | | 5.25+b=22.75 | | 8x+16=100 | | 40-6x=-116 | | g(x)=1482 | | 0.5x*10=0.15 | | 14n^2/2n^2 | | -5(x-6)=-34+3x | | 3m-m^2=2 | | -18x+102=354 | | 0.6-4=2.6 | | 10=0.10x | | 9x+27=100 | | 10/0.10 | | 8+8m=4+8m+8 | | 8+8m=4+8m+4 | | 3x-2+4=70 | | 5n-n=15+7 | | 7x-x=-16-2x | | -7r-8-5r=-13-7r | | 9x+45=100 | | f(x)=(x^7-4x^6)*(x+3)*(x-2) | | 9x+36=100 |